Energy-efficient technologies for thermal treatment and drying of food products - Oleg Burdo; Igor Bezbah; Valentyna Bandura; Sergiy BEZBAH; Viacheslav PETROVSKYI; Petr OSADCHUK (Journal of Central European Agriculture, 2025)
A study of the process of heat treatment, concentration, and drying of food products in a thermomechanical unit with a rotary thermosiphon was conducted. Analysis of experimental data revealed that, compared to convective drying, the dryers with a rotary thermosiphon (RTS) spend most of the energy (69.4%) on moisture evaporation. When drying dispersed products (peas, wheat), energy consumption is lower compared to the energy consumption of existing convective dryers. Energy consumption approaches the minimum when drying at the RTS condenser temperature of Ts = 142.9 °С for different rotation frequencies. In the conducted series of experiments at a rotation frequency of 28 rotations per minute (RPM) and a surface temperature of 142.9 °C, the energy consumption for the process is minimal and reaches 3.2 MJ/kg. Energy consumption is reduced by 832.9 kJ/kg of product when drying cereals that do not require boiling with the use of a thermomechanical aggregate (TMA) with RTS. The total energy consumption of the line is reduced by 30% when using TMA with RTS as a dryer and softener. When using TMA with RTS in the tomato paste production line, fuel consumption can be reduced from 46.5 kg to 30.2 kg. It is also possible to reduce specific energy consumption from 3.9 MJ/kg to 2.6 MJ/kg to intensify the thermomechanical processing of tomato mass by 1.4 times or decrease the processing time from 4,090 s to 2,900 s.